2020
DOI: 10.1021/acs.est.0c05624
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly High Indoor HONO Concentrations Associated with Photochemical NO2 Transformation on Glass Windows

Abstract: Nitrous acid (HONO) is an important gaseous pollutant contributing to indoor air pollution because it causes adverse health effects and is the main source of hydroxyl radicals (OH). Here, we present direct measurements of HONO produced through light-induced heterogeneous reactions of NO2 with grime adsorbed on glass window. The uptake coefficients of NO2 [γ­(NO2)] on the glass plates from the kitchen increased markedly from (2.3 ± 0.1) × 10–6 at 0% RH to (4.1 ± 0.5) × 10–6 at 90% RH. We report a significant qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 43 publications
(97 reference statements)
7
66
0
Order By: Relevance
“…14,15 Apart from only focusing on the concentrations of HAP, "Home-Chem" is becoming an issue in recent studies. 16,17 In indoor, chemical and physical transformations of air pollutants could occur under certain conditions. For example, a latest study found light-induced heterogeneous reactions of NO 2 with grime on glass window could produce HONO.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Apart from only focusing on the concentrations of HAP, "Home-Chem" is becoming an issue in recent studies. 16,17 In indoor, chemical and physical transformations of air pollutants could occur under certain conditions. For example, a latest study found light-induced heterogeneous reactions of NO 2 with grime on glass window could produce HONO.…”
Section: Introductionmentioning
confidence: 99%
“…While for rural areas which are far from industry sources and have limited motor vehicles, indoor solid fuel burning and/or smoking contributed most to HAP 14,15 . Apart from only focusing on the concentrations of HAP, “Home‐Chem” is becoming an issue in recent studies 16,17 . In indoor, chemical and physical transformations of air pollutants could occur under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a recent study which indicated that organic lm materials collected in a kitchen are highly viscous. 64 The higher viscosity of the intact lm may slow heterogeneous chemistry such as ozone reactions with C]C bonds and heterogeneous NO 2 conversion to HONO. The concentration of ozone in the house was, on average, fairly low: $8 AE 18 ppb.…”
Section: Ozonolysismentioning
confidence: 99%
“…However, recent studies discovered the higher‐than‐expected concentrations of hydroxyl radical (OH) in special indoor settings, due primarily to the photolysis of combustion‐related nitrous acid (HONO) 20 and/or terpene‐ozone reactions during cleaning 21 . Besides, the high surface‐to‐volume ratios indoors enhance the possibility and significance of surface reactions, 22,23 accelerating heterogeneous formation of HONO for example 24,25 . Recently, by applying novel tools for studying atmospheric chemistry to indoor chemistry, researchers have made compelling breakthroughs in revealing indoor dynamic source emissions and ozone chemistry 26‐28 .…”
Section: Introductionmentioning
confidence: 99%